Argonaute 4 as an Effector Protein in RNA-Directed DNA Methylation in Human Cells - Chalertpet, Kanwalat; Pin-on, Piyapat; Aporntewan, Chatchawit; Patchsung, Maturada; Ingrungruanglert, Praewphan; Israsena, Nipan; Mutirangura, Apiwat (Frontiers in Genetics, 2019)
DNA methylation of specific genome locations contributes to the distinct functions of multicellular organisms. DNA methylation can be governed by RNA-dependent DNA methylation (RdDM). RdDM is carried out by endogenous small-RNA-guided epigenomic editing complexes that add a methyl group to a precise DNA location. In plants, the Argonaute 4 (AGO4) protein is one of the main catalytic components involved in RdDM. Although siRNA or shRNA has been shown to be able to guide DNA methylation in human cells, AGO protein-regulated RdDM in humans has not yet been evaluated. This study aimed to identify a key regulatory AGO protein involved in human RdDM by bioinformatics and to explore its function in RdDM by a combination of AGO4 knockdown, Alu siRNA transfection, AGO4-expressing plasmid transfection, chromatin immunoprecipitation, cell-penetrating peptide-tagged AGO4 (CPP-AGO4) combined Alu sgRNA transfection, and methylation analyses. We found that first, human AGO4 showed stronger genome-wide association with DNA methylation than AGO1-AGO3. Second, endogenous AGO4 depletion demethylated DNA of known AGO4 bound loci. Finally, exogenous AGO4 de novo methylated the bound DNA sequences. Therefore, we discovered that AGO4 plays a role in human RdDM.